Secondary data collected from Ifraz-2 Erbil for Drinking Water Quality Assessment - Omer Tahir, Lanja (Zanco Journal of Pure and Applied Sciences, 2022)
The goal of the current study was to use the Water Quality Index (WQI) to evaluate the overall drinking water quality status in Erbil City, Kurdistan Region of Iraq, by estimating the quality of the Greater Zab River (raw water) and the water treatment plant WTP at Ifraz-2 on the Greater Zab River, a tributary of the Tigris River. Thirteen physicochemical parameters, including turbidity, pH, electrical conductivity, total dissolved solids, total hardness, calcium, magnesium, alkalinity, chloride, sodium, potassium, nitrate, and sulfate, were evaluated between 2010 and 2021 using the WQI. The calculated WQI for the Greater Zab River's raw water quality ranged from (140.532) to (422.455) and the calculated WQI for WTP (Ifraz-2) ranged from (44.197) to (69.118). Accordingly, the results of Greater Zab River water were categorized as "very poor," "poor," and "unsuitable" for drinking purposes during the studied period (2010–2021). Furthermore, the results of the computed WQI for WTP of (Ifraz-2) are classified as "Excellent" and "Good". According to WQI, the WTP of Ifraz-2 from the current study was of good quality and suitable for consumption by humans. As a result, the efficiency (E%) of the Ifraz-2 WTP was found to be more efficient in 2016 (89.49%) than in other years and suitable for drinking. Except for a few samples, the physicochemical quality of most drinking water samples during the current study was within WHO limits.